Discussion - White, Ross; O'Connell, Chris; Cressey, Michael (Scottish Archaeological Internet Reports, 2014)
The reconstruction of the local ecology of Dun Law has demonstrated that by the time of the construction of Dere Street, Dun Law was a wet environment and the natural woodland that once covered the area was already substantially denuded. The relative lack of wood would have had an impact on the Roman programme of road construction. The method used at Dun Law amply demonstrates the use of local materials. Dere Street was in use during the post-Roman period and there are numerous references in the medieval period attesting to the longevity of the road.